Psycho-physiological factors as predictors of sport prominence and excellence among student-athletes in southwestern, Nigeria (2017)
This study investigated psycho-physiological factors as predictors of sport prominence and excellence among student-athletes in Southwestern, Nigeria. Psychological factors are goal setting and self-efficacy, while physiological factors are muscular strength, muscular endurance and body composition. Expost-facto research design was used for the study. Purposive sampling technique was used to select 1604 university athletes matriculated students who have represented the institutions in NUGA. The instruments used were Goal Setting in Sport Questionnaire (GS1SQ), Sport Self Confidence Questionnaire (SSCQ), ICHPER.SD Children/Youth Fitness Test. Five hypotheses were tested at 0.05 level of significance. Data were analysed using inferential statistic of regression. The combined effect of the independent variables (both psychological and physiological factors) yielded coefficient of R2: 0.43 and 0.46 respectively and this translated into 43% and 46% of the total variance on sport prominence and excellence. The F-value (F(3.1600) = 25.49. P< 0.05) was found to be significant. Four out of five independent variables tested had significant contributions (P< 0.05): goal setting (fi = .18, t=6.68), self-efficacy (fi =.058, t= 2.19)f muscular strength (β =.06, t=2.07) and muscular endurance (β = . 19, t=6.94) to sport prominence and excellence. However, body composition had no significant contribution. Based on the result of the findings, it was recommended that both psychological and physiological factors intervention support be given student-athletes in order to enhance sport performance, prominence and excellence